Two new species of Oswaldocruzia (Nematoda, Molineidae) parasitising lizards in Ukraine - Svitin, Roman (Zootaxa, 2017)
Two new species, Oswaldocruzia lisnykiensis sp. n. and Oswaldocruzia lacertica sp. n., are described from Anguis fragilis L. (Reptilia: Anquidae) and Lacerta agilis L. (Reptilia: Lacertidae) respectively. Both species belong to the Palaearctic group of species which have spicules divided in three main branches (blade, fork and shoe) with fork division above its distal third. The new species differs from all previously known Palaearctic species by several morphological characters: type of caudal bursa (type III in O. lisnykiensis and type I in O. lacertica), shape of spicules (blade distally divided into four tips and specific shape of shoe) and synlophe structure (narrow cervical alae consist of three crests in both species). Illustrated descriptions of O. lisnykiensis and O. lacertica based on 63 and 38 specimens respectively are presented. Host specificity and geographical distribution of the species are discussed. O. dispar is considered as a species inquirenda.